Design of new class of regular biorthogonal wavelet filter banks using generalized and hybrid lifting structures. Issue 1 (December 2015) - Gawande, Jayanand; Rahulkar, Amol; Holambe, Raghunath
Abstract This paper proposed modified generalized lifting structure and hybrid lifting scheme in order to construct two-channel one-dimensional wavelet filter banks. The first structure is designed using general halfband polynomial by imposing any number of vanishing moments. The generalized even-step and odd-step lifting structure is derived separately to obtain FIR filter banks. The second approach is based on the combination of individual even-step and odd-step lifting structure called as hybrid lifting structure to improve the frequency response of filters. In this paper, the examples based on two-step, three-step, four-step, five-step and six-step lifting schemes are analyzed to investigate the properties of the wavelet filter banks. It is observed that the hybrid lifting scheme achieves more symmetry, more regularity, lower frame bounds ratio, good time–frequency localization and better frequency selectivity than individual two-step, three-step and five-step lifting schemes.